SOLVING THE STUDENTS WRITING SKILL WITH TECHNOLOGY ASSISTANT: THE FUZZY DELPHI APPROACH - Nor Arifah Che Wahab,; Abdul Rasid Jamian, (Journal of Islamic, Social, Economics and Development, 2023)
The development of strong writing skills in primary school students is essential for their academic success and future opportunities Writing skills play a vital role in primary school students' academic success and future opportunities as they enable them to effectively communicate, express their thoughts and ideas, and demonstrate their understanding of various subjects. This study aims at getting expert consensus and opinions on elements of writing skills problem solutions based on technology. This study uses 7 expert scale to gather input from 7 experts in different education fields in Malaysia using Fuzzy Delphi process. The assessment received a total of 8 key construct of the questionnaire. The Fuzzy Delphi method Logic Software (FUDELO) has been used for data analysis. The data were analysed using a triangle fuzzy number and a ranking of the defuzzification process with each construct elements. The results of the study and the consensus of the experts show that the Agreement's value is in a good level. This shows that elements of writing skills solutions have been well-received by experts. The elements agreed upon by the experts in consensus are arranged in order of ranking process.